2017
DOI: 10.1007/164_2017_9
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor and Pain

Abstract: There is a critical need for new analgesics acting through new mechanisms of action, which could increase the efficacy respect to existing therapies and/or reduce their unwanted effects. Current preclinical evidence supports the modulatory role of the sigma-1 receptor (σR) in nociception, mainly based on the pain-attenuated phenotype of σR knockout mice and on the antinociceptive effect exerted by σR antagonists on pain of different etiology, very consistently in neuropathic pain, but also in nociceptive, infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 133 publications
0
55
0
Order By: Relevance
“…In this regard, several preclinical studies have shown that sigma-1 receptor (σ1R) may play a critical role in the development of pathological pain (Merlos et al., 2017). Interestingly, the genetic ablation of σ1R in peripheral injury-induced pathological pain models resulted in either attenuation or avoidance of pain-related behaviors in mice (Cendán et al., 2005; de la Puente et al., 2009; Entrena et al., 2009a; Nieto et al., 2012; Tejada et al., 2014; Gris et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several preclinical studies have shown that sigma-1 receptor (σ1R) may play a critical role in the development of pathological pain (Merlos et al., 2017). Interestingly, the genetic ablation of σ1R in peripheral injury-induced pathological pain models resulted in either attenuation or avoidance of pain-related behaviors in mice (Cendán et al., 2005; de la Puente et al., 2009; Entrena et al., 2009a; Nieto et al., 2012; Tejada et al., 2014; Gris et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Beside its direct effects in causing pain hypersensitivity, it was also found that σ1R tonically modulates opioid analgesia. Both of these effects offer the potential for pharmaceutical modulation of σ1R in treatment of pain (Romero et al, ; Merlos et al, ). Specifically, its peripheral effects are the most interesting, as the strongest expression of σ1R in the nervous system was observed in primary afferent DRG neurons (Bangaru et al, ; Mavlyutov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, its peripheral effects are the most interesting, as the strongest expression of σ1R in the nervous system was observed in primary afferent DRG neurons (Bangaru et al, ; Mavlyutov et al, ). In DRG neurons, it causes modulation of the activity of receptors for neurotransmitters and different types of ion channels, thus modulating the perception of pain (Merlos et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sigma-1 receptor (σ 1 R) has been described as the first ligand-regulated molecular chaperone located at the endoplasmic reticulum and plasma membranes whose activity is regulated in an agonist-antagonist manner. The σ 1 R is expressed in key areas for pain control and there is cumulative evidence supporting an involvement of the σ 1 R mainly in two kinds of pain conditions: (1) those involving sensitization, e.g., after sensitization with capsaicin or formalin or following nerve injury where σ 1 R antagonists by themselves inhibit pain behaviors in the absence of opioids (Romero et al, 2012; Vidal-Torres et al, 2014; Gris et al, 2016); and (2) in acute pain conditions after the application of mechanical (paw pressure test) or thermal (tail-flick and hot plate tests) nociceptive stimuli, where σ 1 R antagonists by themselves fail to modify the nociceptive thresholds but enhance opioid-induced antinociception (Sánchez-Fernández et al, 2013; Vidal-Torres et al, 2013; Merlos et al, 2017; Sánchez-Fernández et al, 2017).…”
Section: Introductionmentioning
confidence: 99%